2008
DOI: 10.1037/0735-7036.122.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of face-like patterns in the giant panda (Ailuropoda melanoleuca).

Abstract: The black-and-white pattern of the giant panda's (Ailuropoda melanoleuca) fur is a conspicuous signal and may be used for mate-choice and intraspecific communication. Here the authors examined whether they have the perceptual and cognitive potential to make use of this information. Two juvenile subjects were trained on several discrimination problems in steps of increasing difficulty, whereby the stimuli required to discriminate ranged from geometric figures to pairs of differently orientated ellipses, pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…However, Clark (2013) reviewed the field of marine mammal (primarily bottlenose dolphin and California sea lion, Zalophus californianus) cognition and proposed that knowledge of various species' cognitive skills could and should be used to develop appropriate cognitive enrichment. Cognitive research on other species could be applied in a similar fashion; for example we have a growing knowledge of the cognitive skills of elephants, Elephas maximus, Loxodonta africana (Foerder, Galloway, Barthel, Moore, & Reiss, 2011;Perdue, Talbot, Stone, & Beran, 2012;Plotnik, Lair, Suphachoksahakun, & de Waal, 2001), giant pandas, Ailuropoda melanoleuca (Dungl, Schratter, & Huber, 2008;Perdue, Snyder, Pratte, Marr, & Maple, 2009) and black bears, Ursus americanus (Johnson-Ulrich et al, 2016;Vonk & Beran, 2012;Vonk, Jett, & Mosteller, 2012). There has also been substantial work on the cognition (mainly physical cognition) of corvid birds (Clayton & Emery, 2005;Taylor, 2014).…”
Section: Cognitive Research As Enrichmentmentioning
confidence: 99%
“…However, Clark (2013) reviewed the field of marine mammal (primarily bottlenose dolphin and California sea lion, Zalophus californianus) cognition and proposed that knowledge of various species' cognitive skills could and should be used to develop appropriate cognitive enrichment. Cognitive research on other species could be applied in a similar fashion; for example we have a growing knowledge of the cognitive skills of elephants, Elephas maximus, Loxodonta africana (Foerder, Galloway, Barthel, Moore, & Reiss, 2011;Perdue, Talbot, Stone, & Beran, 2012;Plotnik, Lair, Suphachoksahakun, & de Waal, 2001), giant pandas, Ailuropoda melanoleuca (Dungl, Schratter, & Huber, 2008;Perdue, Snyder, Pratte, Marr, & Maple, 2009) and black bears, Ursus americanus (Johnson-Ulrich et al, 2016;Vonk & Beran, 2012;Vonk, Jett, & Mosteller, 2012). There has also been substantial work on the cognition (mainly physical cognition) of corvid birds (Clayton & Emery, 2005;Taylor, 2014).…”
Section: Cognitive Research As Enrichmentmentioning
confidence: 99%
“…For example, there is relatively little known about bear cognition. This has begun to change in recent years as more empirical studies have been carried out with giant pandas [2,3,4,5,6] and black bears [7,8,9,10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Giant pandas exhibit marking behaviour by peeling bark or disturbing the soil with their claws and directly transfer visual information through body language 20 , 21 . In addition, pandas can discriminate between black-and-white objects with only subtle differences in shape, implying they can perception face-like stimuli 22 . However, previous research has shown that giant pandas cannot recognize themselves in a mirror but instead consider the image to be a separate conspecific individual, indicating they do not have the capacity of self-recognition 23 .…”
Section: Introductionmentioning
confidence: 99%